Arborizing vessels in a targetoid hemosiderotic hemangioma: mistaken dermoscopic diagnosis of basal cell carcinoma - Maria Leonor Enei; Francisco Paschoal; Rodrigo Valdes (Mattioli1885, 2017)
Targetoid hemosiderotic hemangioma (THH) or hobnail hemangioma (HH) is a benign vascular lesion that presents with the classical clinical presentation of a ring-shaped tumor having a targetoid appearance, with a central purple-brown papule surrounded by a thin pale area and an ecchymotic ring on the outside. Dermoscopic features and patterns of HH have been documented and have proven to be sufficient to establish a clinical diagnosis in many cases. We present a facial lesion in which both the clinical presentation and dermoscopy were atypical. The presence of arborizing vessels in the dermoscopic pattern, never before described for this lesion, led us to the diagnosis of basocellular carcinoma (BCC). We also report the changes in this pattern experienced over 12 months of progression and their correlation with the histopathologic findings.